2022
DOI: 10.3390/vaccines10111792
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine-Related Vogt–Koyanagi–Harada Disease Complicated by Central Serous Chorioretinopathy during Treatment Course: Case Report and Literature Review

Abstract: With the promotion of mass COVID-19 vaccination in the elimination of the SARS-CoV-2 pandemic, new side effects, including ocular complications, are emerging. In this study, we report on a 62-year-old Chinese man who developed Vogt–Koyanagi–Harada (VKH) disease six days after his third dose of an inactivated COVID-19 vaccine, with a preceding severe headache and tinnitus. His medical history included tuberculosis 20 years prior and hypertension. Systemic prednisone was administered, resulting in completely rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…As related to vaccination against the coronavirus disease 2019 (COVID- 19), this was implemented to eliminate the SARS-CoV-2 pandemic, providing significant protection against infection and the development of multi-organ acute respiratory distress syndrome. However, subsequent studies have demonstrated potential adverse events in vaccinated patients, including ocular complications: non-arteritic anterior ischemic optic neuropathy (NAION), central serous chorioretinopathy (CSC), and Vogt-Koyanagi-Harada (VKH) disease have been reported [2][3][4][5]7].…”
Section: Introductionmentioning
confidence: 99%
“…As related to vaccination against the coronavirus disease 2019 (COVID- 19), this was implemented to eliminate the SARS-CoV-2 pandemic, providing significant protection against infection and the development of multi-organ acute respiratory distress syndrome. However, subsequent studies have demonstrated potential adverse events in vaccinated patients, including ocular complications: non-arteritic anterior ischemic optic neuropathy (NAION), central serous chorioretinopathy (CSC), and Vogt-Koyanagi-Harada (VKH) disease have been reported [2][3][4][5]7].…”
Section: Introductionmentioning
confidence: 99%